2010
DOI: 10.1097/mej.0b013e32832e67d6
|View full text |Cite
|
Sign up to set email alerts
|

Are emergency department visits really a teachable moment? Smoking cessation promotion in emergency department

Abstract: ED-based counseling for smoking cessation was as effective as that performed in the OC setting. Referral of smokers from the ED to a smoking cessation program was unsuccessful in our patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…This may explain why only 27% of physicians surveyed in this study reported that they routinely advised smokers to quit. Although evidence of the long-term efficacy of smoking cessation counseling in the ED has been limited [ 18 - 22 ], one recent study found that, in the short-term, ED-based counseling for smoking cessation was as effective as counseling performed in an outpatient clinic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may explain why only 27% of physicians surveyed in this study reported that they routinely advised smokers to quit. Although evidence of the long-term efficacy of smoking cessation counseling in the ED has been limited [ 18 - 22 ], one recent study found that, in the short-term, ED-based counseling for smoking cessation was as effective as counseling performed in an outpatient clinic [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In both ED and primary care settings, much of the literature on patient-provider communication about smoking is situated within targeted smoking cessation interventions [ 19 , 23 - 26 ]. Fewer studies have described how ED providers offer smoking counseling spontaneously, within ongoing health care interactions [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in addition to their primary acute-care role, EDs appear as potential places to provide preventive health care [3][6]. Because screening is a component of secondary disease prevention, many attempts have been made to implement ED screening programs for a range of conditions including depression [7], alcohol abuse [8], smoking [9], intimate partner violence [10], diabetes [11], hypertension [12] and more recently HIV infection in the USA [13].…”
Section: Introductionmentioning
confidence: 99%
“…One study found ED-based counselling to be as efficacious as that delivered in an outpatient setting. 23 Similarly, a recent systematic review demonstrated that exposure to ED-based cessation interventions resulted in greater cessation rates than the US National Health Interview Survey average 6 , but that studies are highly heterogeneous in intervention type, follow-up timing, outcome assessment and control groups used. In a metaanalysis, ED-initiated tobacco control that incorporated motivational interviewing with booster telephone calls trended towards tobacco abstinence for up to 12 months.…”
Section: Intervention Preferencesmentioning
confidence: 99%